Rethinking the approach to economic justifications under the EU's free movement rules - Arrowsmith, Sue
The ECJ has frequently stated that it is a general rule that “economic” aims are precluded as justifications for restrictions on free movement. This on its face suggests that free movement always and automatically trumps national economic interests. However, in reality the Court’s approach to balancing these different interests is much more complex: often, and increasingly, interests of an economic nature are in fact recognised in the Court’s case law. This paper suggests that this rule precluding economic aims as justifications therefore requires reformulating. It is argued that this is necessary not merely to reflect the reality of the case law, but also to improve the transparency and quality of judicial decision-making. The paper then also examines how the current prohibition might be reformulated in light of both the policy considerations underlying the current formulation (embodying a degree of caution in accepting economic interests) and the problems with that formulation. It is suggested that it is appropriate to maintain a kind of rule against economic objectives, but a more nuanced one concerned solely with measures that have a protectionist aim – the original target of the “general” rule prohibiting economic justifications. On the other hand, with measures that do not have protectionist aims, recognition of economic objectives should be determined on a case-by-case basis that is attuned to the wide variety of economic interests that exist. An important group of measures within the latter category comprises those directed at protection of Member States’ budgetary interests. These warrant special attention and the paper also examines how these interests can be suitably addressed within the context of the framework proposed above. According to the Court’s current approach, in theory budgetary justifications are prohibited as a consequence of the rule against economic justifications in general. However, it is explained that, like certain other economic justifications, they are in reality often permitted, being allowed in certain defined and specific circumstances. Further, where they are permitted, the Court limits application of the proportionality test in that it does not examine whether alternative means might be used to recoup the lost revenue. In this way the Court balances national economic interests and free movement but avoids various constitutional and practical difficulties of applying a proportionality test to do so. It is proposed that the Court should continue with this approach. However, it needs to acknowledge that it does accept justifications that are budgetary in nature, and that these constitute exceptions to any general rule against budgetary justifications. It might also be appropriate, further, to accept budgetary justifications as a general rule in addition to existing, specific, budgetary justifications whenever there is a significant impact on a specific programme budget. However, it is acknowledged that this approach is not consistent with the case law.